GE_GERICHTE P/25348/2018 vom 27. Juni 2023 - GE Cour de justice (2023)
ESCROQUERIE;ATTEINTE ASTUCIEUSE AUX INTÉRÊTS PÉCUNIAIRES;SUSPENSION DE L'EXÉCUTION DE LA PEINE;TRAITEMENT AMBULATOIRE | CP.151; CP.146.al1; CP.47; CP.19.al2; CP.56.al1; CP.63.al1; CP.63.al2; CP.63a.al1